2017
DOI: 10.5614/sostek.itbj.2017.16.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Peran Teknologi Informasi Dalam Perkembangan Dakwah Mahasiswa

Abstract: ABSTRAKPeran teknologi informasi sangat penting dalam pelaksanaan dakwah di kalanagn mahasiswa ITB. Dakwah dengan menggunakan IT akan memberikan hasil yang lebih baik dibandingkan dakwah secara manual. Daya jangkau dakwah dengan IT lebih jauh, efektif, dan sederhana. Dakwah dengan cara lama, seperti metode ceramah langsung atau dengan media televisi membutuhkan ruang dan waktu khusus. Bahkan, tidak jarang membutuhkan dana yang besar. Penelitian ini bertujuan untuk memberikan pilihan bahwa dakwah dengan menggun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 0 publications
0
5
0
3
Order By: Relevance
“…That preaching through new media is more accessible and easily accepted by the public. through the media of da'wah it gives better results and is quickly accessed by the public because the reach of da'wah through technology is more effective and simpler (Purwanto, 2017). It is the same as the article written by Sufia Widi which explains the features in gadgets that can make human activities easier, including Islamic applications that have started to appear and are easily found in gadget content.…”
Section: Resultsmentioning
confidence: 96%
“…That preaching through new media is more accessible and easily accepted by the public. through the media of da'wah it gives better results and is quickly accessed by the public because the reach of da'wah through technology is more effective and simpler (Purwanto, 2017). It is the same as the article written by Sufia Widi which explains the features in gadgets that can make human activities easier, including Islamic applications that have started to appear and are easily found in gadget content.…”
Section: Resultsmentioning
confidence: 96%
“…The ar-rahnu industry is generally keeping up with technological development, such as the use of digital platforms to attract more customers, and this could be identified as a factor that has increased customer acceptance of ar-rahnu, which contributes indirectly to the ar-rahnu's positive financial performance. Several previous studies, such as those by Purwanto et al (2017) and Muhammadin et al (2015), found that implementing new technology improved financial performance. However, these studies were limited to large corporations.…”
Section: Introductionmentioning
confidence: 92%
“…Model komunikasi yang dibentuk juga melibatkan banyak manusia. Antara satu dengan lainnya bisa saling bertukar informasi, bertukar pikiran atau menjadi wadah berdiskusi tanpa harus bertatap muka [3]. Hal ini tentunya akan menjadi suatu hal yang cocok dalam penyebaran dakwah di era pandemi covid-19.…”
Section: Pendahuluanunclassified